IMPLEMENTATION E-CRM FOR SELLING OF VIRGIN COCONUT OIL IN MAZZURY INDUSTRY - Khairani, Siti Fadillah; Saputra, Herman; Rohminatin, Rohminatin (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2024)
Abstract: The development of information technology has experienced rapid growth, especially the internet. The internet has made significant contributions, particularly in the business sector. The intense business competition and the rapid advancement of information technology have facilitated greater accessibility for customers in choosing industries. The Mazzuri Batu Bara industry is a business that sells coconut oil products and handcrafted items made from coconut. However, Mazzuri Batu Bara has not yet implemented services that make it easier for customers to purchase products efficiently and still relies on manual processes. Sales reports are recorded in ledgers, making the process inefficient for maintaining organized records. Customers are required to visit the industry in person to learn about the products available, which means they are unaware of the latest discounts and products on offer. One of the strategies to improve service and operations is to implement a Customer Relationship Management (CRM) system. The objective of this research is to assess the operability of the system design that has been developed. With the CRM design, sales can be enhanced to better meet customer needs. This system is designed to facilitate Mazzuri Batu Bara in selling products, processing data digitally, and improving customer service loyalty by retaining existing customers and attracting new ones.Keywords: coconut oil; e-crm; industry mazzuri batu bara.  Abstrak:  Perkembangan teknologi informasi telah mengalami pertumbuhan yang sangat pesat terutama internet. Internet memberikan kontribusi yang sangat membantu dalam bidang bisnis. Persaingan bisnis yang ketat dan pesatnya pertumbuhan teknologi informasi memberikan kemudahan aksesbilitas pelanggan dalam memilih industri. Industri Mazzuri Batu Bara adalah usaha bisnis  yang menjual produk minyak kelapa dan kerajinan tangan dari kelapa. Industri Mazzuri Batu Bara belum menerapkan layanan yang memudahkan pelanggan untuk membeli barang dengan mudah dan masih menggunakan layanan secara manual, data laporan penjualan masih digunakan dalam buku besar sehingga tidak efisien untuk melakukan pencatatan yang tertata rapi, pelanggan harus datang langsung ke industri untuk mengetahui produk apa yang dijual maka pelanggan tidak mengetahui diskon terbaru dan produk yang dijual di industri. Salah satu upaya dalam meningkatkan pelayanan dan operasional adalah dengan menerapkan konsep Customer Relationship Management (CRM). Tujuan pada penelitian ini adalah operabilitas hasil desain sistem yang telah dibuat. Dengan desain Customer Relationship Management (CRM), dapat meningkatkan penjualan dalam memenuhi kebutuhan pelanggan. Sistem ini dibuat untuk memudahkan Industri Mazzuri Batu Bara dalam menjual produk, mengolah data secara komputerisasi dan dapat meningkatkan loyalitas pelayanan kepada pelanggan dalam mempertahankan pelanggan dan menarik pelanggan baru.Kata kunci: e-crm; industri mazzuri batu bara; minyak kelapa.